Stochastic Generation Of Hourly Wind Speed Time Series. - A, Shamshad; W. M. A., Wan Hussin; M. A., Bawadi; S. A., Mohd. Sanusi (2003)
In the present study hourly wind speed data of Kuala Terengganu in Peninsular Malaysia are simulated by using transition matrix approach of Markovian process. The wind speed time series is divided into various states based on certain criteria.